IoT-Enabled Smart Waste Sorting System Using Proximity and Ultrasonic Sensors for Campus Environments - Donny Sanjaya; Rio Herlambang; Heykel Prayogi Timanta G.S; Muhammad Khoiril Amri (Yayasan Asmin Intelektual Berkah, 2026)
The rapid increase in population and urbanization has led to significant challenges in waste management, especially in developing countries like Indonesia. According to the World Bank, global waste generation reached 2.56 billion metric tons in 2022, and under a business-as-usual scenario, this figure is projected to rise to 3.86 billion metric tons by 2050. At Politeknik Negeri Medan, a growing concern has emerged over the inefficiency of traditional waste disposal systems, which often result in environmental pollution and ineffective sorting processes. This paper proposes the design of an IoT-based Smart Waste Sorting System tailored for campus environments as a pilot model for broader smart city implementation. The proposed system integrates IoT technologies such as sensors, microcontrollers, and wireless communication to automatically detect, identify, and sort waste into appropriate categories: organic, inorganic, and recyclable. Data from smart bins are transmitted in real-time to a central monitoring dashboard, enabling efficient waste collection scheduling and reducing overflow incidents. The system also includes a fire detection feature for safety and a data analytics module to forecast waste generation trends. By implementing this system at Politeknik Negeri Medan, we aim to enhance environmental awareness, optimize waste handling processes, and support sustainable campus initiatives. The results demonstrate that IoT integration in waste sorting contributes significantly to improving operational efficiency and can serve as a scalable model for smart waste management in urban areas.